2020
DOI: 10.1038/s41443-020-0338-1
|View full text |Cite
|
Sign up to set email alerts
|

Penile implant infection prevention part II: device coatings have changed the game

Abstract: The single most important factor in the reduction of penile implant infections has been the infection retardant coatings. Virtually every inflatable penile prosthesis (IPP) sold for the last 15 years in America has been coated and the device infection rate has dropped over 50% to less than 1% in experienced implanter practices. The vast majority of penile implants are contaminated with bacteria at time of surgery and the bacteria live within the implant spaces in a quiescent fashion protected by a biofilm secr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Since Mulcahy’s study in 2000, advances in antibiosis, device design, and surgical technique have resulted in a significant reduction in infection risk ( 11 , 12 ). The advent of antibiotic impregnated devices in 2001 has led to a significant decrease in primary placement infection rates to 1–4% ( 36 - 38 ). Although there are no direct comparisons, it is reasonable to conclude that this reduction is conferred to IS patients as well ( 39 ).…”
Section: Resultsmentioning
confidence: 99%
“…Since Mulcahy’s study in 2000, advances in antibiosis, device design, and surgical technique have resulted in a significant reduction in infection risk ( 11 , 12 ). The advent of antibiotic impregnated devices in 2001 has led to a significant decrease in primary placement infection rates to 1–4% ( 36 - 38 ). Although there are no direct comparisons, it is reasonable to conclude that this reduction is conferred to IS patients as well ( 39 ).…”
Section: Resultsmentioning
confidence: 99%
“…While no standardized irrigation protocol exists, some authors have reported modified techniques of antiseptic washout during removal and replacement of infected prosthetic with high reinfection-free success rates (>80%) across various cohorts ( 11 , 12 , 14 ). What’s more, there have also been reported successes with salvage surgery without any antibiotic irrigation ( 48 ). This begs the question whether antibiotics are necessary during manual irrigation.…”
Section: Treatment Selection and Technique For Immediate Salvage Surgerymentioning
confidence: 99%
“…Advances in PP designs with the use of infection-retardant coatings have also led to significant decreases in overall PP infection rates (40). Boston Scientific (Marlborough, MA) introduced the InhibiZone technology into the AMS 700 inflatable PP in 2001, which contains minocycline and rifampin (41).…”
Section: Current Applications To Reduce Biofilm Attachmentmentioning
confidence: 99%